Determination of vibration analysis in single and double cracked cantilever numerical beam. (2022) - Mohanraj, M.; Pandiyarajan, R.; Jayakumar, K.S.; Antony Prabu, D.; Sabarish, S.; Sankaralingam, T.
Abstract: Constructions are debilitated by crack. At the point when the Crack size builds, the construction turns out to be exceptionally failed; at last the design may Crackdown because of moment Crack. Thusly, Crack recognition is vital. The target of this investigation is free vibration examination of cracked cantilever beam utilizing FEM. This research has focused on both the cases namely single edge crack as well as double edge crack and the frequency characteristics are determined for various mode of crack location and the crack depth by ANSYS software.